Emotion regulation in self-injurious youth: a tale of two circuits - Santana-Gonzalez, Carmen; Ranatunga, Janani; Nguyen, Giang; Greiskalns, Brianna; Das, Natasha; Lattimer, Evan; Maurice, Matthew; Yi, Gina; Zietlow, Anna-Lena; Eckstein, Monika; Zilverstand, Anna; Quevedo, Karina (Psychiatry research. Neuroimaging, 2025)
Two emotion regulation (ER) networks, the amygdala and ventral striatum (VS) circuits underpin defensive and reward processes related to non-suicidal self-injury (NSSI). Youth who engaged in non-suicidal self-injury behavior (NSSIB) and healthy controls either watched images passively (passive condition) or increased their positive affect during positive/neutral images and decreased their negative affect during negative and self-harm images (regulate condition) in the scanner. NSSI youth showed higher amygdala to precuneus and inferior parietal lobe (IPL) connectivity while regulating emotions during self-harm images, a pattern which was associated with higher self-injury frequency. NSSI youth showed higher VS connectivity to the fusiform gyrus and parahippocampus while regulating emotions elicited by self-harm and positive images, which was in turn linked to higher self-harm frequency and relief after NSSI. Higher amygdala-precuneus and IPL connectivity in NSSI youth suggest greater self-identification with, or difficulty regulating negative affect elicited by, self-injury images. High VS-fusiform gyrus and parahippocampus connectivity during positive and self-harm images implies reward anomalies and/or greater effort to regulate positive affect. VS circuit's’ links to relief and NSSIB frequency suggest VS reward-based learning as biomarker of NSSIB endurance. We discovered ER mechanisms in adolescents with NSSIB and promising targets for effective NSSIB treatment.
Online veröffentlicht: 18. Dezember 2024
Gesehen am 17.04.2025